Sport nutrition an introduction to energy production and performance - Jeukendrup, Asker E. 1969- (Human Kinetics, 2010)
"The new edition of Sport Nutrition: An Introduction to Energy Production and Performance presents the principles, background, and rationale for current nutrition guidelines specifically for athletes. Using a physiological basis, this text provides an in-depth look at the science behind sport nutrition. Students will come away with a comprehensive understanding of nutrition as it relates to sport and the influence of nutrition on exercise performance, training, and recovery